1988
DOI: 10.1038/332454a0
|View full text |Cite
|
Sign up to set email alerts
|

The neurotrophic factor neuroleukin is 90% homologous with phosphohexose isomerase

Abstract: Neuroleukin (NLK) is a protein of relative molecular mass (Mr) 56,000 (56K) secreted by denervated rat muscle and found in large amounts in muscle, brain, heart and kidneys. The protein is a neurotrophic factor for spinal and sensory neurons and a lymphokine product of lectin-stimulated T-cells. It also induces immunoglobulin secretion by human mononuclear cells. Molecular clones of NLK have been expressed in monkey COS cells and the product was shown to have the same biological and biochemical properties as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
129
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(133 citation statements)
references
References 9 publications
3
129
0
1
Order By: Relevance
“…Molecular cloning and sequencing have identified PGI as a motility factor: i.e., autocrine motility factor (AMF; ref. 5), also known as and neuroleukin (6) or maturation factors (7). AMF/PGI is also a multifunctional cytokine that exhibits multifunctional growth factor-like activity via a unique cognate 78 kDa (gp78) seven-transmembrane glycoprotein receptor (autocrine motility factor receptor, AMFR; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular cloning and sequencing have identified PGI as a motility factor: i.e., autocrine motility factor (AMF; ref. 5), also known as and neuroleukin (6) or maturation factors (7). AMF/PGI is also a multifunctional cytokine that exhibits multifunctional growth factor-like activity via a unique cognate 78 kDa (gp78) seven-transmembrane glycoprotein receptor (autocrine motility factor receptor, AMFR; ref.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 We purified AMF from conditioned medium of murine metastatic fibrosarcoma, and demonstrated that AMF is identical to phosphohexose isomerase (PHI), also designated as glucose-6-phosphate isomerase (GPI), which is a ubiquitous enzyme catalyzing the conversion of glucose-6-phosphate to fructose-6-phosphate. 5 AMF/PHI has also been found to be identical to neuroleukin (NLK), 6,7 a neurotrophic growth factor that supports the survival of spinal and sensory neurons, 8 and maturation factor (MF) mediating the differentiation of human myeloid leukemic HL-60 cells to terminal monocytic cells, 9 suggesting that this cytokine is multifunctional, probably dependent on the target cells. AMF/PHI activities have shown to be elevated in the serum or urine of patients with disseminated malignant tumors such as gastrointestinal, kidney, breast, colorectal, and lung carcinomas, 10,11 , thereby being useful as a tumor-dissemination marker.…”
mentioning
confidence: 99%
“…This central role in the metabolism of phosphorylated sugars explains the strong impact of PGI deficiency in humans (6,7), as well as the interest as a therapeutic target in parasite metabolism (8). The PGI polypeptide chain, or perhaps a variation thereof, also has extracellular roles as neuroleukin, autocrine motility factor, and differentiation and maturation mediator (9)(10)(11)(12). These proteins promote antibody secretion by mononuclear cells, tumor cell motility, and differentiation of leukemia cells and a promyelocytic cell line (HL-60 cells), respectively.…”
mentioning
confidence: 99%